Application prospect of advanced oxidation technology in wet process phosphoric acid production. Issue 6 (December 2022) - Liu, Xinxin; Wu, Fenghui; Qu, Guangfei; Jin, Caiyue; Liu, Ye; Kuang, Lingrui; Li, Hailin; Chen, Xiuping; Wang, Zuoliang; Cheng, Yinhan
Abstract: Phosphoric acid is a world-wide strategic resource related to the country's livelihood, and the demand for phosphoric acid is increasing. The efficient and sufficient extraction of phosphoric acid from medium and low-grade phosphate rock has become one of the main research techniques. This paper summarizes the conventional and unconventional phosphoric acid processing technologies, compares their advantages and disadvantages, analyzes their applicability to different phosphate rocks and phosphorus recovery, and describes the migration and transformation characteristics of pollutants in by-products. In order to improve the phosphorus recovery and reduce the environmental pollution risk of by-products, the method of using advanced oxidation technology to enhance the recovery of phosphorus from medium and low-grade phosphate rock is proposed. The residual amount of pollutants and environmental pollution risks of by-products under the conditions of advanced oxidation technology were analyzed, aiming to provide new theoretical support for the upgrading and transformation of phosphoric acid production technology and process in phosphorus chemical enterprises. Graphical Abstract: ga1 Highlights: Comprehensive summary and analysis of common phosphoric acid production processes. Analysis of the current status of unconventional phosphoric acid production. Advanced oxidation technology promotes phosphoric acid production from phosphate rock. Analysis of the application prospects of advanced oxidation technology in phosphorus resource production.